2018
DOI: 10.1080/10717544.2018.1477860
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic carbon monoxide delivery based on hemoglobin vesicles ameliorates acute pancreatitis in mice via the regulation of macrophage and neutrophil activity

Abstract: Macrophages play a central role in various inflammatory disorders and are broadly divided into two subpopulations, M1 and M2 macrophage. In the healing process in acute inflammatory disorders, shifting the production of M1 macrophages to M2 macrophages is desirable, because M1 macrophages secrete pro-inflammatory cytokines, whilst the M2 variety secrete anti-inflammatory cytokines. Previous findings indicate that when macrophages are treated with carbon monoxide (CO), the secretion of anti-inflammatory cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…Afterward, the anti‐inflammatory effect of CO releasing nanocomposites has also been confirmed in inflammation‐related animal models such as colitis and acute pancreatitis . Nagao et al investigated the therapeutic potential of CO‐hemoglobin vesicles (CO‐HbV) in dextran sulfate sodium (DSS)‐induced murine colitis models.…”
Section: Carbon Monoxide Releasing Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Afterward, the anti‐inflammatory effect of CO releasing nanocomposites has also been confirmed in inflammation‐related animal models such as colitis and acute pancreatitis . Nagao et al investigated the therapeutic potential of CO‐hemoglobin vesicles (CO‐HbV) in dextran sulfate sodium (DSS)‐induced murine colitis models.…”
Section: Carbon Monoxide Releasing Nanomaterialsmentioning
confidence: 99%
“…The protective effects of CO‐HbV on colitis can owe to the reduction of neutrophil accumulation as well as the decrease of oxidative injuries. Taguchi et al reported that in acute pancreatitis mice model, CO derived from CO‐HbV could not only attenuate the infiltration of neutrophils in pancreatic tissue, but also skew the polarization of macrophage toward an M2‐like phenotype, ultimately leading to a dramatical suppression in the intensity of pancreatic injury. Apart from the attenuation of acute pancreatitis, CO‐HbV nanocomposites could also diminish the pancreatitis‐associated damage to distal organs including liver, kidneys and lungs .…”
Section: Carbon Monoxide Releasing Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study proved the protective effect of CO-HbV in AP-induced multiorgan damage. [63,64] In another study, two-generation 5 (G5) polyamidoamine (PAMAM) dendrimers with distinct surface groups G5-OH and G4.5-COOH were investigated for their potential to treat pancreatic injury in caerulein-induced mouse model of AP. Both the dendrimers significantly reduced inflammatory infiltration of macrophages into the pancreatic tissues thereby decreasing the pathological changes in pancreas.…”
Section: Nanotechnology and Targeted Delivery In Apmentioning
confidence: 99%
“…It may be due to the inhibition of systemic inflammation, lung neutrophil infiltration and HMGB-1 production. Biomimetic CO delivery based on the hemoglobin vesicle was also found to improve acute pancreatitis treatment by regulating the polarization of its macrophages toward M2-type (Taguchi et al., 2018 ). Peritoneal puncture and drainage can improve the therapeutic effect of acute pancreatitis by regulating the M2-type polarization of macrophages (Liu et al., 2018 ), which suggests that macrophages might serve as therapeutic target in pancreatitis.…”
Section: Formulation Approaches For Acute Pancreatitismentioning
confidence: 99%